Model Mediasi Minat Beli pada Pengaruh Brand Image, Brand Ambassador, dan Store Atmosphere terhadap Keputusan Pembelian - Ayu, Annisa Ika Diah; Sari, Diana; Nofiyanti, Rina (Journal of Trends Economics and Accounting Research, 2025)
In an era of increasingly fierce global competition, the fashion retail industry is experiencing rapid development, including in Indonesia. Where everyone chooses clothing styles according to their desires, ranging from casual, formal, to semi- formal styles. The purpose of this study is to determine and analyze the influence of brand image, brand ambassadors, and store atmosphere on purchasing decisions, the influence of brand image, brand ambassadors, and store atmosphere on purchase intention, the influence of purchase intention on purchase decisions and the influence of brand image, brand ambassadors, and store atmosphere on purchase decisions through purchase intention as an intervening variable. The research method uses primary data obtained from distributing questionnaires to 150 respondents. Respondents are consumers of Uniqlo products who are at least 18 years old and domiciled in the Bekasi City area. The analytical tools used in this study are convergent validity test, discriminant validity test, reliability test, R- Square test, predictive relevance test, path coefficient test, indirect effect test, and goodness of fit test. The results of this study indicate that brand image and store atmosphere influence purchasing decisions. However, brand ambassadors do not influence purchasing decisions. Meanwhile, brand image, brand ambassador, and store atmosphere influence purchasing interest. Purchase interest influences purchasing decisions. Meanwhile, brand ambassadors and store atmosphere influence purchasing decisions through purchase interest. However, brand image does not influence purchasing decisions through purchase intention.